2016
DOI: 10.3892/ijmm.2016.2804
|View full text |Cite
|
Sign up to set email alerts
|

Humulus japonicus inhibits the progression of Alzheimer's disease in a APP/PS1 transgenic mouse model

Abstract: Humulus japonicus Siebold & Zucc. (HJ) has traditionally been administered to patients with pulmonary disease, skin disease and hypertension in Korea, and it is considered to exert anti-inflammatory, antioxidant, antimicrobial and anti-mycobacterial effects. However, its effects against Alzheimer's disease (AD) have yet to be explored. Thus, this study was carried out to investigate whether HJ has a beneficial effect on the progression of AD in an animal model. A methanolic extract of HJ (500 mg/kg/day) was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…The novel object recognition test was performed as described in previous studies ( 21 , 22 ). The mice were individually habituated to a testing chamber (40×20×20 cm 3 ) with no objects for 5 min and then placed in a testing chamber for 10 min with two identical objects (familiar, acquisition session).…”
Section: Methodsmentioning
confidence: 99%
“…The novel object recognition test was performed as described in previous studies ( 21 , 22 ). The mice were individually habituated to a testing chamber (40×20×20 cm 3 ) with no objects for 5 min and then placed in a testing chamber for 10 min with two identical objects (familiar, acquisition session).…”
Section: Methodsmentioning
confidence: 99%
“…Humulus japonicus , also known as “Japanese hop”, is a perennial herb belonging to the Cannabaceae family and is ubiquitously found in Asian countries, including Korea, Japan, and China [ 50 ]. H. japonicus has long been used in traditional medicine to cure skin diseases, pulmonary tuberculosis, and hypertension [ 50 ].…”
Section: Plant Extracts That Stimulate Adipocyte Browningmentioning
confidence: 99%
“…Humulus japonicus , also known as “Japanese hop”, is a perennial herb belonging to the Cannabaceae family and is ubiquitously found in Asian countries, including Korea, Japan, and China [ 50 ]. H. japonicus has long been used in traditional medicine to cure skin diseases, pulmonary tuberculosis, and hypertension [ 50 ]. Other biological effects of H. japonicus include antimutagenic, antibacterial, antiatheroma, antioxidant, antitumor, antimycobacterial, and anti-inflammatory effects [ 50 , 51 , 52 , 53 , 54 ].…”
Section: Plant Extracts That Stimulate Adipocyte Browningmentioning
confidence: 99%
“…Recent study has shown that the 70% EtOH extract of H. japonicus protects against oxidative stress in vivo and in vitro models of Parkinson’s disease [17] and attenuates neuroinflammation in murine models of Alzheimer’s disease [18]. Dereplication using high performance liquid chromatography coupled with high resolution mass spectrometry (HPLC-HRMS) in natural product research has recently been introduced as a key step in the identification of secondary metabolites in target extracts.…”
Section: Introductionmentioning
confidence: 99%